2023
DOI: 10.1002/cl2.1297
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence and gap map report: Social and Behavior Change Communication (SBCC) interventions for strengthening HIV prevention and research among adolescent girls and young women (AGYW) in low‐ and middle‐income countries (LMICs)

Abstract: Background Adolescent girls and young women (AGYW), aged 15–24 years, are disproportionately affected by HIV and other sexual and reproductive health (SRH) risks due to varying social, cultural, and economic factors that affect their choices and shape their knowledge, understanding, and practices with regard to their health. Socio‐Behavioral Change Communication (SBCC) interventions targeted at strengthening the capabilities of individuals and their networks have supported the demand and uptake of prevention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 472 publications
0
3
0
Order By: Relevance
“…Molyneaux et al identified collaboration as essential for strengthening the health system [ 37 ]. The NTD agenda extends beyond parasitic diseases, with a massive annual delivery of medicines to a billion people, mainly targeting the poorest, aligning with the 2030 UN SDGs for universal health coverage; adapting to global events and policy changes is crucial for sustained progress, requiring innovative thinking within health systems, led by policymakers, managers, and frontline health workers, which necessitates effective collaboration among partners involved [ 3 , 11 , 18 , 38 ]. Such partnerships between health workers and educators showcase the potential for leveraging existing networks within communities to achieve program goals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Molyneaux et al identified collaboration as essential for strengthening the health system [ 37 ]. The NTD agenda extends beyond parasitic diseases, with a massive annual delivery of medicines to a billion people, mainly targeting the poorest, aligning with the 2030 UN SDGs for universal health coverage; adapting to global events and policy changes is crucial for sustained progress, requiring innovative thinking within health systems, led by policymakers, managers, and frontline health workers, which necessitates effective collaboration among partners involved [ 3 , 11 , 18 , 38 ]. Such partnerships between health workers and educators showcase the potential for leveraging existing networks within communities to achieve program goals.…”
Section: Discussionmentioning
confidence: 99%
“…Health workers acknowledged effective communication with community leaders and stakeholders, facilitating program acceptance and local support for field officers, and this aligns with findings in other programs [ 36 ]. Findings from studies indicated that integrating technology and innovative communication methods can serve as valuable tools to improve the effectiveness of MDA programs for STH and SCH [ 35 , 38 ]. This enhancement encompasses various aspects, including heightened awareness, knowledge dissemination, acceptance, demand generation, behavior change communication (BCC), feedback mechanisms (such as monitoring cards), quality assurance (ensuring drug availability), accountability (through reporting), and sustainability (facilitated by stakeholder engagement) [ 38 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation